Potret Kontestasi Filsafat Islam dalam Era Sains Modern - Usuluddin, Win (IAIN Ponorogo, 2012)
The modern scientists have been considering philosophy as meaningless field for long time because it questions non exact field, not real and not actual. Therefore, it is believed that they do not need philosophy anymore. Islamic philosophy discussing a lot about mystic and metaphysic also get significant challenge in the era of modern science. This paper will try to discuss the construction built by Islamic philosophy particularly in its contestation in the era of modern science. Some of that constructive efforts are by demonstrating and introducing Islamic philosophy in more actual sense, for example by remapping Islamic philosophy followed by rearranging Islamic epistemology in order to reveal that Islamic philosophy does not only limit the object of knowledge on physical object but also nonphysic. Hence, we need to discuss the reality of mystical experience intensively in order to explain rationally that the reality of mystical experience is real. Another problem we are going to discuss here is the objectivity and integrity of knowledge in Islamic Philosophy’s view and to make historical reflection in order to build scientific tradition to develop Islamic philosophy in the future.